The Russia–Ukraine Conflict and Its Impact on Indonesia Energy and Food Economy in 2022 - Dharma Feriawan; Ali Maksum (Mahesa Research Center, 2026)
This study examines how the conflict between Russia and Ukraine has affected Indonesia's rising costs for wheat, fertilizer, and oil. The study looks at how domestic policy responses are influenced by global disruptions using a political-economics framework. With an emphasis on oil, wheat, and fertilizer imports, financial statistics and trade data between Russia, Ukraine, and Indonesia were gathered in 2021–2022. Descriptive qualitative approaches, data-gathering techniques, and data-analysis procedures are used in the analysis. According to the findings, the war caused a great deal of instability in the world's oil distribution, which raised Indonesian commodities prices and had a domino impact on the country's food supply chains. The conflict also impacted Indonesia's access to fertilizer raw materials from Russia, the cost of importing oil from Russia, and the purchase of wheat from Ukraine. As a result, fertilizer prices significantly increased, which in turn led necessities like wheat to rise. Overall, the study improves knowledge of how geopolitical conflicts directly affect Indonesia's economic stability through supply vulnerabilities and price escalation, and it emphasizes the need of strategic policy responses to handle external influences.